Structure–metal ion selectivity of rhodamine-based chemosensors. Issue 35 (12th April 2023) - Ghosh, Pritam; Roy, Partha
Abstract : A structure–property correlation between rhodamine-based chemosensors and metal ion selectivity has been discussed here. Abstract : Rhodamine-based chemosensors are widely used for the detection of various metal ions and applied in many fields of science including biological and environmental sciences. Rhodamine derivatives remain colorless and almost nonfluorescent when their spirolactam ring remains in closed form. They become pink or purple and strongly fluorescent upon opening of the ring. A particular metal ion can induce the ring opening process under a set of conditions and the process of selective sensing is dependent on many factors. Differentiation of metal sensing using rhodamine dyes is achieved in various ways which include selection of solvent, pH, mode of interaction with the cations, and so on. We have incorporated more than 140 research articles here to discuss the structure–property correlation of rhodamine based chemosensors. We have tried to correlate metal ion selectivity and structures of the chemosensors for the first time for rhodamine derivatives.